Characterization of Xylanase from Streptomyces spp. Strain C1-3 - ANJA MERYANDINI (Bogor Agricultural University, Indonesia, 2007)
Xylan is the major constituent of hemi cellulose. Several enzymes are needed to hydrolyse xylan completely, including xylanase. Currently, there is an increasing use of this enzyme. This study was carried out to characterize the xylanase from Streptomyces spp. strain C1-3. Results showed that the xylanase displayed its highest activity at pH 3 and 90 0C and was stable up to 10 hours at this conditions. Its activity increased after the addition of Cu2+, Fe2+, and Co2+ under concentration of 1 and 5 mM, respectively. The activity however, decreased after the addition of Mg2+, Ca2+ at 1 mM and Zn2+ at 5 mM. After a test with five kinds of xylan (i.e. from Birchwood, Beechwood, Arabinoxylan, Oat spelt and CMC), the xylanase of Streptomyces spp. C1-3 showed its preferences to Birchwood- and Arabino-xylan. The results showed that the xylanase of Streptomyces spp. C1-3 was characterized as a thermostable acid xylanase. Key words: xylanase, Streptomyces, stability, CMCase